Parkinson's Disease and Neurodegeneration: GABA-Collapse Hypothesis - Błaszczyk, Janusz W. (Frontiers in Neuroscience, 2016)
Neurodegenerative diseases constitute a heterogeneous group of age-related disorders that are characterized by a slow but irreversible deterioration of brain functions. Evidence accumulated over more than two decades has implicated calcium-related homeostatic mechanisms, giving rise to the Ca2+ hypothesis of brain aging and, ultimately, cell death. Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter within the central (CNS), peripheral and enteric nervous systems. It appears to be involved in a wide variety of physiological functions within and outside the nervous system, that are maintained through a complex interaction between GABA and calcium-dependent neurotransmission and cellular metabolic functions. Within CNS the Ca2+/GABA mechanism stabilizes neuronal activity both at cellular and systemic levels. Decline in the Ca2 +/GABA control initiates several cascading processes leading to both weakened protective barriers (in particular the blood-brain barrier) and accumulations of intracellular deposits of calcium and Lewy bodies. Linking such a vital mechanism of synaptic transmission with metabolism (both at cellular and tissue level) by means of a common reciprocal Ca2+/GABA inhibition results in a fragile balance, which is prone to destabilization and auto-destruction. The GABA decline etiology proposed here appears to apply to all human neurodegenerative processes initiated by abnormal intracellular calcium levels. Therefore, the original description of Parkinson’s disease (PD) as due to the selective damage of dopaminergic neurons in the mesencephalon should be updated into the concept of a severe multisystemic neurodegenerative disorder of the nervous system, whose clinical symptoms reflect the localization and progression of the most advanced GABA pathology. A future and more complete therapeutic approach to PD should be aimed first at slowing (or stopping) the progression of Ca2+/GABA functional decline.